The Management and Outcome of Brief Resolved Unexplained Event (BRUE) in Pediatric Intensive Care Unit: A Single Tertiary Center Experience - Alkhayat, Mahmoud; alareefy, Abdulaziz; Alsaad, Abdulaziz; Bashir, Mohammed; Algushaimy, Mohamed; Alfuhigi, Khalid; Alsoqati, Abdulaziz; Aljassim, Nada (International Journal of Innovative Research in Medical Science, 2022)
Objectives: We aim to describe the current practice and management for patients presented with Brief Resolved Unexplained Event (BRUE) & their outcome over three years at the tertiary pediatric intensive care unit. We also looked for the proportion of inappropriate use of BRUE as admission diagnosis and the ratio of low-risk and high-risk BRUE patients in our PICU. Methods: A retrospective cohort study conducted at King Fahad Medical City between 2017 and 2020 that included all infants from 28 days up to one year of age who were admitted with the diagnosis of BRUE to the pediatric intensive care unit (PICU) at King Fahad Medical City (650 admissions per year) over 3 years. All infants with a diagnosis of cyanotic heart disease, infants who are on home oxygen, and infants more than 1 year of age were excluded. The diagnosis of BRUE was defined based on the American Academy of Pediatrics (AAP) BRUE guidelines published in 2016. Results: Over 3 years period, we collected a total of 48 infants. 37 infants were male and 11 females. There was a statistically significant association between BRUE and with history of prematurity or other medical problems. 68.7% of the admission to the PICU did not fit the BRUE diagnosis of AAP 2016. Only 15 infants (31.3%) fit the diagnosis of AAP 2016 of BRUE, with 7 infants out of the 15 (46.7%) fit as low-risk BRUE while 8 infants (53.3%) were fit as high-risk BRUE. Conclusion: Following the AAP guidelines is necessary to avoid over diagnosis of BRUE, especially in the low-risk group that can be managed outside PICU.